I haven't been entirely honest with you - Hart, Miranda, 1972- (Penguin Michael Joseph, 2024)
"Packed with hard-won wisdoms and gentle truths, this is Miranda's honest exploration of the lessons she has learned on her journey from illness to recovery"--Provided by publisher.